PEMBERIAN ETANOL JANGKA PANJANG MENURUNKAN MEMORI KERJA SPASIAL PADA TIKUS - Aswin, Soedjono; Mustofa, Mustofa (Fakultas Kedokteran Universitas Brawijaya, 2008)
Long term ethanol administration may cause morphological changes in the hippocampus, followed by deficit in the hippocampal function including the impairment of memory. The aim of this study is to investigate the changes of spatial working memory of rats after chronic ethanol administration at adolescent age. Twenty five adolescent (30 days of age) male rats (Rattus novergicus) divided randomly into 5 groups : control without treatment (C1), control with treatment (C2), treatment 1 (T1), treatment 2 (T2), treatment 3 (T3) group. Each group consist of 5 rats. C2 group was given physiologic saline, T1, T2, and T3 group were given ethanol with doses 1, 2, and 3 g/kg/day for 30 days by intraperitoneal injection. After chronic ethanol administration the spatial working memory of 5 groups were tested by using 8 arm radial maze for 12 days. Spatial working memory measured by total number of entered arm maze and error A type. The results of this study showed that chronic ethanol administration at adolescent age caused decreasing of spatial working memory of the rats. The total number of entered arms maze and error A type for treatment group (especially P3 ) is higher than control groups (p<0,05). It is concluded that in rats, chronic ethanol administration at adolescent age caused decreasing spatial working memory. Key words : Ethanol, Spatial working memory, Adolescent